Development of a Learning Management System (LMS) Based on Canvas Instructure to Support Students’ Critical Thinking Skills - Aulia Rahma Dewi; Alfi Syahrin Siregar; Rofiki, Imam (Universitas Negeri Surabaya, 2025)
A learning management system (LMS) is a solution for managing learning in the 21st-century education era. Canvas Instructure is an LMS that supports students’ critical thinking skills. This study aims to develop a canvas-based LMS structure on Linear Program material to support the critical thinking skills of grade 11 students. The research method was research and development using the ADDIE development model. The LMS was tested on 22 11th-grade high school students with Linear Program material. The results showed that LMS validation was 89.375% from LMS validation experts and 92.222% from material experts. The average of teachers’ and students’ response questionnaires were 94.36% and 89.37%, respectively. Student evaluation test results obtained a percentage of student completeness of 90.91% with an average of 85.82. Therefore, this LMS is considered valid, effective, and practical for use in supporting the critical thinking skills of grade 11 students in the Linear Program.